Pharmacokinetic Profiles of Active Components After Oral Administration of a Kampo Medicine, Shakuyakukanzoto, to Healthy Adult Japanese Volunteers. Issue 11 (November 2015) - Sadakane, Chiharu; Watanabe, Junko; Fukutake, Miwako; Nisimura, Hiroaki; Maemura, Kazuya; Kase, Yoshio; Kono, Toru
ABSTRACT: Shakuyakukanzoto (SKT), a traditional Japanese (Kampo) medicine, has been used by patients with muscle cramps and abdominal pains. In this trial, we analyzed plasma concentrations of active components after SKT was administered as a single oral dose of 2.5 or 5.0 g/day per person. The study was a randomized, open-label, two-arm, two-period, crossover trial conducted in healthy Japanese volunteers. Albiflorin (ALB), paeoniflorin (PAE), glycycoumarin (GCM), isoliquiritigenin (ILG), glycyrrhetic acid (GA), and glycyrrhetic acid-3-O-monoglucuronide were targeted, and the plasma concentration of each component was measured using a liquid chromatography-tandem mass spectrometry method. The pharmacokinetic parameters were calculated, and the linearity was assessed. All targeted components were detected in the plasma after oral administration of SKT. ALB, PAE, GCM, and ILG were detected at an early stage. The linearity was observed for the maximum plasma concentration of GCM, ILG, and GA and for the area under the plasma concentration-time curve of GA. In this trial, we demonstrated for the first time in humans that these components were absorbed into the blood after oral administration of SKT. The results of this pharmacokinetic trial in humans are also important and useful for understanding the mechanism of action of SKT, verifying the active components predicted in basic research, and conducting pharmacokinetics and safety studies in the future.